2019
DOI: 10.3390/d11110210
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Habitat Loss and Mining on the Distribution of Endemic Species of Amphibians and Reptiles in Mexico

Abstract: Mexico holds an exceptional diversity and endemicity of amphibian and reptile species, but several factors pose a threat to their conservation. Here, we produced ecological niche models for 179 Mexican endemic amphibian and reptile species and examined the impact of habitat loss and mining activities on their projected potential distributions, resulting in their extant distributions. We compared extant species distributions to the area required to conserve a minimum proportion of the species distribution. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Records with incorrect georeferenced data were fixed using the Google Satellite layer in QGIS, only when the collectors verified the exact location. This process aimed to obtain a clean and debugged database that met appropriate standards for ecological niche modeling [45][46][47], biogeographic analyses [48,49], and Red List Assessment [12,16,21], by Darwin Core guidelines (https://dwc.tdwg.org/).…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Records with incorrect georeferenced data were fixed using the Google Satellite layer in QGIS, only when the collectors verified the exact location. This process aimed to obtain a clean and debugged database that met appropriate standards for ecological niche modeling [45][46][47], biogeographic analyses [48,49], and Red List Assessment [12,16,21], by Darwin Core guidelines (https://dwc.tdwg.org/).…”
Section: Plos Onementioning
confidence: 99%
“…Ecuador is one of the countries with the highest number of amphibian species [12][13][14][15]. Ecuadorian amphibians are considered among the most threatened in South America, due to increased rates of habitat loss and deforestation for cattle raising, agriculture, mining, and oil exploitation [16][17][18][19][20][21]. Some historically conspicuous genera (harlequin frogs [Atelopus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Habitat loss has impacted several species of terrestrial vertebrates in Mexico, especially endemic species in the Transvolcanic Mexican Belt, Mexican High Plateau, and the Humid Coastal Plains and Hills of the Gulf of Mexico, and the effects appear to be cumulative (i.e., not just recent habitat loss) ( Mayani-Parás et al 2021 ). The loss of habitat, and in particular forest habitats, has negatively affected the amphibians and reptiles of Mexico ( Lara-Tufiño et al 2019 ; Mayani-Parás et al 2019 ), and a high proportion of endangered amphibians in Mexico are found in areas that have experienced transformation to agriculture or urbanization ( Londoño-Murcia and Sánchez-Cordero 2011 ) and these trends are likely to continue or increase in the future ( Mendoza-Ponce et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reptile populations in the tropics are influenced by island size (Ricklefs and Lovette 1999), elevation (Fauth et al, 1989; Ricklefs and Lovette, 1999), geography (Moser et al, 2018), topography (Ricklefs and Lovette 1999) and vegetation structure (Herrera-Montes and Brokaw 2010). Furthermore, reptiles face a multitude of threats, including but not limited to predation by invasive species (Gibbons et al, 2000), habitat disturbance/loss (Mayani-Parás et al, 2019), human disturbance/persecution (Alves et al, 2012; Atwood et al, 2020), and climate change (Urban, 2015). In the Caribbean, hurricanes in particular are predicted to increase in frequency and severity by the end of the 21 st century (Webster et al, 2005; Bender et al, 2010).…”
Section: Introductionmentioning
confidence: 99%